Vibration of circular plates with mixed edge conditions. Part III: Localized frequency curve veering phenomena - Sompornjaroensuk, Yos (วารสารวิจัย มทร. กรุงเทพ, 2021)
This paper aims to investigate and examine the phenomenon of mode localization and frequency curve veering for vibratory circular plates with mixed edge conditions. An important characteristic of curve veering is that when two loci of the curves approach each other as system parameters vary, they often exactly cross (intersections) or abruptly diverse away (avoided crossings). The latter case is termed as curve veering. Thus, in the present paper, the carried out results reveal a significant effect on the occurrence of curve veering possibilities due to support length variations that can be detected by plotting the variation of frequency parameter against the angle provided the circumferential plate support by means of finite element method with discretized refinement model.